Edukasi Relaksasi Napas Balloon Blowing untuk Meningkatkan Saturasi Oksigen pada Pasien Post Operasi dengan General Anestesi di RSUD Cilacap - Khofifah Shinta Anggraini; Made Suandika; Emiliani Elsi Jerau (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Postoperative complications following general anesthesia, especially those affecting the respiratory system, present a significant challenge in healthcare services, as they can lead to oxygen desaturation and hypoxemia, ultimately impairing vital organ function. One intervention to improve oxygen saturation is the balloon blowing technique. This community service activity aimed to provide education on balloon blowing breathing relaxation techniques to enhance oxygen saturation in postoperative patients under general anesthesia. The method included a 5-minute educational session and a 3–5 minute demonstration of the balloon blowing technique. Measurements of knowledge levels and oxygen saturation were conducted before and after the intervention. The results showed a significant improvement: prior to the education, 70% of participants (21 individuals) experienced decreased oxygen saturation, while after the intervention, all participants (100%) showed increased oxygen saturation. Knowledge levels also improved, with 70% of participants initially in the low category, increasing to 100% in the good category after the education.